Process fixation in Ukraine in the context of the COVID-19 pandemic - Parneta, Oksana; luzyk, Valentyn (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
This work is devoted to the study of the issue of recording the trial in a pandemic.  The main innovations that ensure the hearing of cases taking into account the circumstances around the world in 2020 are outlined.  Effective means and ways to ensure the rational functioning of the judicial system in Ukraine have been identified. The topic is relevant because on March 12, 2020 quarantine was introduced in Ukraine. On March 17, 2020 the Council of Judges of Ukraine adopted a decision approving the Recommendations on establishing a special regime for the courts of Ukraine to protect the population of Ukraine from acute respiratory diseases and coronavirus COVID-19, which is classified as a particularly dangerous infectious disease. The Council of Judges of Ukraine recommends establishing a special regime for the courts of Ukraine, as well as expanding the laws of Ukraine on certain rulescourt work and court hearings for the period of quarantine. For the period of quarantine, cases were postponed for the safety of the population, so the trial could take the form of a video conference. For the safety of citizens, the courts appealed to the parties not to visit the courts, but to file a motion to adjourn the case, or to request a hearing in the absence of the parties. Since the introduction of quarantine, a whole wave of so-called "quarantine" legislation has emerged, and during the quarantine, video conferencing platforms have been created. Regarding the creation of video platforms, they were: EasyCon, ESITS, Zoom. The legislation of Ukraine provided for certain guarantees of legality during court hearings. The rules are included in the Constitution of Ukraine, namely the recording of the case by technical means and also in Article 247 of the СPK the process of fixing by technical means is entered. It is an official activity of the court, which provides for the consistent reproduction of the court session. During the quarantine established by the Cabinet of Ministers of Ukraine in order to prevent the spread of the disease, the participants may participate in the court hearing in the form of a video conference outside the court premises. Thus, since the introduction of quarantine in Ukraine, a whole wave of "quarantine" legislation has emerged. The innovations were created for the safety of people and to prevent the spread of the virus. Several platforms for video conferencing were created that could be used in the courts, as well as other new rules that had to be followed during quarantine.